2009
DOI: 10.1093/toxsci/kfp254
|View full text |Cite
|
Sign up to set email alerts
|

Airway Exposure to Silica-Coated TiO2 Nanoparticles Induces Pulmonary Neutrophilia in Mice

Abstract: The importance of nanotechnologies and engineered nanoparticles has grown rapidly. It is therefore crucial to acquire up-to-date knowledge of the possible harmful health effects of these materials. Since a multitude of different types of nanosized titanium dioxide (TiO(2)) particles are used in industry, we explored their inflammatory potential using mouse and cell models. BALB/c mice were exposed by inhalation for 2 h, 2 h on 4 consecutive days, or 2 h on 4 consecutive days for 4 weeks to several commercial T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(100 citation statements)
references
References 29 publications
7
90
2
1
Order By: Relevance
“…Conflicting data showing that particle size is not related to inflammatory potential has also been reported [22,23,39,57,102]. It is likely that the factors involved in nanotoxicity are complex and interactive.…”
Section: Primary Sizementioning
confidence: 99%
See 2 more Smart Citations
“…Conflicting data showing that particle size is not related to inflammatory potential has also been reported [22,23,39,57,102]. It is likely that the factors involved in nanotoxicity are complex and interactive.…”
Section: Primary Sizementioning
confidence: 99%
“…However, these changes were minimal when cells were R, rutile; A, anatase; B, brookite; it, intranasal instillation; INH, inhalation; NPs, nanoparticles; BW, body weight; "-", independent factor; "+", dependent factor. treated with uncoated rutile TNPs, anatase TNPs, and SiO 2 NPs [22]. UV Titan (rutile TiO2 modified with Al, Si, Zr and coated with polyalcohol) is reported to produce prolonged lung inflammation in dams and developmental neurotoxicity in pups [71].…”
Section: Surface Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, initial toxicological data indicate that there is reason for caution. Pulmonary inflammation has been observed in animals exposed to titanium dioxide (TiO 2 ) and carbon nanotubes (CNT) (Shvedova, Kisin et al 2005, Chou, Hsiao et al 2008, Rossi, Pylkkanen et al 2010. Other studies have shown that nanoparticles can translocate to the circulatory system and to the brain and cause oxidative stress (Elder, Gelein et al 2006, Wang, Liu et al 2008.…”
Section: Background For This Studymentioning
confidence: 99%
“…Compared with their bulk counterparts, nanomaterials are often more toxic (Grassian et al, 2006;Pan et al, 2007). For example, a number of toxicological studies using rats have shown that exposure to nanodots induces greater inflammatory and cytotoxic effects than larger-sized particles at equivalent mass concentrations (Grassian et al, 2006;Gillespie et al, 2010;Rossi et al, 2010). Most nanomaterial toxicity studies have focused on nanodots (i.e., particles of various shapes with no predominant dimension, or 0D), and only a few studies have addressed the toxicity of elongated rod-like (1D) nanoparticles (Magrez et al, 2009;Song et al, 2010) or compared 1D nanomaterials with their 0D counterparts (Chithrani et al,2006;Pal et al, 2007;Ispas et al, 2009;Simon-Deckers et al, 2009).…”
Section: Introductionmentioning
confidence: 99%